Design is how it works : how the smartest companies turn products into icons - Greene, Jay (Portfolio, 2010)
Jay Greene shows how important it is to build a culture in which design is more than an after-the-fact concern, it's part of your company's DNA. Drawing on interviews with top executives, Greene illuminates the methods of companies that rely on design to stand out in their industry. -- [book jacket]